Regulation of adrenergic system in adipose tissue in obesity - Cabral, André Morais Sarmento Borges (2018)
The prevalence of obesity is dramatically increasing worldwide, and is associated with an increased risk of cardiovascular disease and metabolic disorders. Adipose tissue is recognized as a major endocrine and secretory organ, producing a variety of adipokines which modulate energy homeostasis, lipid physiology, inflammation and immune function. It has been recently highlighted that the pattern of adipose tissue distribution (visceral or subcutaneous) might be a predictive of health risk. Visceral obesity is considered to be more pro-inflammatory and more strongly associated with cardiometabolic risk. The catecholamines (CA), adrenaline (AD) and noradrenaline (NA) are the major regulators of lipidic metabolism in adipocytes, also affecting the differentiation and proliferation of these cells and the secretion of adipokines. The recent finding that adipocytes are able to produce CA opens a new perspective about the role of these amines in obesity. The aim of this study was to investigate the localization and expression of two of the most important enzymes involved in CA synthesis, tyrosine hydroxylase (TH) and phenylethanolamine N-methyltrasnferase (PNMT), in metabolically distinct adipose tissue depots, using C57BL6 mice as dietary-induced obesity model. Two groups of male and female C57BL/6 mice with about 22-23 g were used. During 12 or 16 weeks, one group was fed with a high-fat diet (HFD, 45% lipids, 20% proteins and 35% carbohydrates) and the other with a standard diet (SD, 13% lipids, 20% proteins and 67% carbohydrates). After 12 and 16 weeks, mice were respectively overweighed or obese (15% and 45% of weight gain, respectively). All the animals were sacrificed and visceral and subcutaneous adipose tissues (VAT and SAT) collected after diet interventions. The number of adipocytes producing TH or PNMT, and cellular localization of these enzymes were evaluated by immunhistochemistry. mRNA levels of both enzymes were assessed by quantitative real-time PCR. In this study, animals fed with the HFD showed an increase of adipocyte areas in both VAT and SAT, compared with those fed with a standard diet (SD). In addition, contrary to subcutaneous, visceral adipocyte areas significantly increased after 16 weeks in comparison with 12 weeks of dietary treatments. The immunohistochemistry assays showed that both TH and PNMT are cytoplasmic enzymes, being located in the perinuclear area and along the cell membrane. Protein levels of these two enzymes were differently affected by the type of diet. The number of adipocytes expressing TH decreased with the HFD, whereas those expressing PNMT increased, in comparison with the SD. Protein TH levels were only significantly modified by global comparison between VAT and SAT, regardless of the diet. Indeed, in these conditions, SAT presented a higher number of TH expressing adipocytes than VAT. On the other hand, whereas the two adipose tissues expressed similar PNMT mRNA levels, VAT presented lower values of TH mRNA than SAT. In conclusion, results obtained with this study showed that the expression of both TH and PNMT in adipose tissue is differently modulated on visceral and subcutaneous adipose depots and is dependent on the diet type.